Inheritance of seed size in watermelon populations (2020)
Seed size is an important agronomic trait and is applicable to different abilities. Small seeds guarantee the greater use of the pulp, while larger seeds facilitate sowing. However, there is little work on the genetic control of this characteristic in watermelon. The objective of this work was to study the seed size inheritance in watermelon populations by crossing contrasting genotypes, seeking to gain information to provide technical support during the selection of seed size for the development of new watermelon genotypes. The seed lengths of six populations, P1, P2, F1, F2, BC1 and BC2, were measured using the GENES software segregating and nonsegregating generations procedure. This trait is controlled by two genes with incomplete dominance. In addition, depending on the populations studied, inheritance for the characteristic in question may behave differently. Nevertheless, the selection of superior individuals within populations can be performed based on this phenotype, which allows the exploitation of these individuals within breeding programs to develop lines or hybrids.